Conservation agriculture can enhance maize productivity in high-rainfall regions: Nine-year evidence from Northern Zambia - Mhlanga, Blessing; Kalala, Kelvin; Thierfelder, Christian (Elsevier, 2025)
Conservation Agriculture (CA) is often perceived to underperform in high-rainfall regions, leading to limited research and promotion in such environments. In Zambia, most CA studies have focused on Southern and Eastern regions, with little emphasis on Northern Zambia, despite its need for improved productivity and sustainability. Understanding CA's performance in high-rainfall areas is critical for sustainable agricultural intensification. This nine-year study in Northern Zambia evaluated the effects of cropping systems and rainfall variability on maize productivity, soil pH, and soil organic carbon (SOC) using a randomized complete block design. Three CA-based cropping systems were compared to two conventional tillage systems. Yearly precipitation showed significant interannual variability, influencing maize grain yield in a complex cubic response pattern, highlighting nonlinear interactions between cropping systems and rainfall. CA-based systems generally outperformed conventional tillage, particularly in moderate to below-average rainfall years, demonstrating resilience under drier conditions. However, conventional ridge and furrow tillage outperformed CA systems during exceptionally high rainfall years, likely due to better drainage. Over time, yield declines indicated soil fertility depletion, though CA-based systems slowed this decline compared to conventional tillage. Rainfall was identified as a primary driver of cropping system performance, with CA-based systems performing better in below-average to moderate rainfall years and tillage-based systems in excessive rainfall years. Soil pH increased significantly under basin planting at 5–15 cm and 30–60 cm depths, while SOC accumulation was highest at 60–90 cm under ridge and furrow tillage. These findings suggest that while CA can enhance maize productivity in high-rainfall regions, site-specific management strategies are needed to mitigate waterlogging and sustain soil fertility. Further research is needed to explore soil-water dynamics and optimize CA practices under varying rainfall regimes.